1995
DOI: 10.3109/00016349509021176
|View full text |Cite
|
Sign up to set email alerts
|

Severely impaired fetal growth is preceded by maternal hemodynamic maladaptation in very early pregnancy

Abstract: Maternal hemodynamic adaptation in the first weeks of pregnancy is defective in IUGR pregnancies, presumably associated with a concomitant inadequacy of the vascular filling state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
98
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 17 publications
6
98
0
3
Order By: Relevance
“…In pregnancies with IUGR, compared to those with normal fetal growth, the maternal cardiac output is lower 5 . Duvekot et al 6 examined 10 women, early in the first trimester, who subsequently had normal pregnancies and four women who subsequently developed IUGR. They found a suboptimal increase in cardiac output and smaller left atrial diameter, an index of preload and thus plasma volume expansion in pregnancies that subsequently developed fetal growth restriction 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In pregnancies with IUGR, compared to those with normal fetal growth, the maternal cardiac output is lower 5 . Duvekot et al 6 examined 10 women, early in the first trimester, who subsequently had normal pregnancies and four women who subsequently developed IUGR. They found a suboptimal increase in cardiac output and smaller left atrial diameter, an index of preload and thus plasma volume expansion in pregnancies that subsequently developed fetal growth restriction 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine growth restriction (IUGR) is an important predictor of neonatal morbidity and mortality (Vorherr, 1982;Kramer, 1987). Severely growth restricted fetuses are at increased risk of stillbirth, and those born alive are at increased risk of neonatal death as well as short-term morbidity from hypoglycemia, hypocalcemia, and polycythemia (Kramer, 1987;Duvekot et al, 1995;Kramer, 2003). Over a longer term, IUGR infants tend to have small but permanent deficits in growth and neurocognitive development.…”
Section: Introductionmentioning
confidence: 99%
“…Over a longer term, IUGR infants tend to have small but permanent deficits in growth and neurocognitive development. Recent studies have demonstrated a relationship between impaired growth in the prenatal and early postnatal period and serious disease risks, including noninsulindependent diabetes, hypertension, and coronary heart disease (Duvekot et al, 1995;Kramer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Seguindo esse raciocínio, alguns autores encontraram aumento da resistência periférica em gestantes com fetos com restrição de crescimento intra-uterino 2,11 . Em nosso estudo, os comportamentos da resistência periférica e da pressão arterial média foram diferentes, quando a gestação resultou em recém-nascido PIG ou AIG.…”
Section: Discussionunclassified
“…A hipervolemia fisiológica da gravidez garante o suporte de oxigênio e nutrientes para o feto e protege a mãe contra os efeitos danosos da diminuição do retorno venoso, decorrente da compressão uterina durante a gestação e da perda sangüínea no parto. Duvekot et al 2 demonstraram que gestantes com volemia inalterada ou pouco aumentada, no período da embriogênese, têm fetos com restrição de crescimento intra-útero. Em gestantes normais e em portadoras de hipertensão arterial crônica há nítida correlação entre a expansão do volume plasmático e o peso fetal 3 .…”
unclassified